PROTEKSI MINYAK IKAN LEMURU, MINYAK KELAPA SAWIT, DAN BUNGKIL SAWIT TERHADAP pH DAN NH3DALAM RUMEN SAPI PERANAKAN ONGOLE - Catur Suci Purwati (Buletin Peternakan, 2016)
The aimed of this research is to know the influence of protection lemuru oil, palm oil, and palm oil cake to pH and NH3in the rumen of the Ongole. The material were used in this study werecomulated rumenfemale cows with average body weight of 289.33 ± 28.34 kg as many as 3 heads. Latin square experiment design was applied on 3 treatments. Fermented rice straw (FRS), basal concentrate (BC), and protected materials of Indian sardine oil (ISO), palm oil (PO), and palmkernel cake (PKC) were used as a feed ingredient.  Treatments were: P1 = FRS 40% + BC 60% (BC 95% + PO 5%); P2 = FRS 40% + BC 60% (BC 95% + ISO 5%) ; P3 = FRS 40% + BC 60% (BC 90% + PKC 10%). Parameters measured were pH and NH3. Latin square experiment design was applied on 3 treatments.Conclusions of this study are pH and NH3remain stable, meaning lemuru addition of fish oil, palm oil, and palm oil cake is protected not disturb the digestive process in the cow rumen fistulated onggole breedparticular.(Key word: Indian sardine oil, NH3, Palm kernel cake, Palm oil, pH, Protection)